Customer intention to purchase halal cosmetics in Malaysia - Meng, Xiang (2014)
The main objective of this research is to examine the factors influencing customer intention to purchase halal cosmetics in Malaysia especially by University students. The research investigates on four factors that affect the intention to purchase halal cosmetics in Malaysia which are attitude, subjective norm, perceived behavioral control and brand awareness. Data were collected from 400 female students in Universiti Utara Malaysia. The internal consistency reliability test of Cronbach’s Alpha indicated that all scale items were proven reliable. Correlation and Multiple Regression were used to examine the relationship between independent variables and dependent variable. The results showed that there are positive relationships between the four factors and intention to purchase halal cosmetics. The result also showed the attitude is the most important factor in affecting customer intention to purchase halal cosmetics in Malaysia.